The Cosmopolitan World of the Quran and Late Antique Humanism - Todd Lawson (Religions, 2021)
The purpose of this essay is to demonstrate how two distinct but deeply related literary genres, which had become especially prominent in the 7th century Nile-to-Oxus region, have left an enduring impression on the form and contents of the Quran. By saying this, it is not intended to suggest that the Quran was “influenced” by this or that extraneous or extra-textual phenomenon. Rather, it is suggested that, along the lines of the Quran’s own theory of revelation, it speaks through Muḥammad, “the language of his people” (Q14:4). Stated another away, the Quran employs themes and structures from both epic and apocalypse that would have been familiar to its audience in order to reveal and make clear its most cherished sacred truths, among which are: the Oneness of God, the Oneness of Religion and the Oneness of Humanity. Epic and apocalypse, then, emerge as features of the cultural and imaginative language of the intended audience of the Quran, just as Arabic is its “linguistic” language.